2021
DOI: 10.1186/s13063-020-04982-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of four different strategies for SARS-CoV-2 surveillance in the general population (CoV-Surv Study): a structured summary of a study protocol for a cluster-randomised, two-factorial controlled trial

Abstract: Objectives In this cluster-randomised controlled study (CoV-Surv Study), four different “active” SARS-CoV-2 testing strategies for general population surveillance are evaluated for their effectiveness in determining and predicting the prevalence of SARS-CoV-2 infections in a given population. In addition, the costs and cost-effectiveness of the four surveillance strategies will be assessed. Further, this trial is supplemented by a qualitative component to determine the acceptability of each str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Applying smart digital disease management might have the potential to substantially reduce the throughput in the ambulatory health-care system. 149 This approach could be an option in regions with a fast growing prevalence of patients with chronic diseases or in regions with a reduced density of medical services. Ultimately, this approach to disease management might be the optional virtual solution for ambulatory care in patients with chronic and metabolic diseases during a pandemic.…”
Section: Long-term Consequences and Monitoring After Covid-19mentioning
confidence: 99%
“…Applying smart digital disease management might have the potential to substantially reduce the throughput in the ambulatory health-care system. 149 This approach could be an option in regions with a fast growing prevalence of patients with chronic diseases or in regions with a reduced density of medical services. Ultimately, this approach to disease management might be the optional virtual solution for ambulatory care in patients with chronic and metabolic diseases during a pandemic.…”
Section: Long-term Consequences and Monitoring After Covid-19mentioning
confidence: 99%
“…These high proportions of asymptomatic individuals represent a challenge for implementing successful surveillance strategies, that have mainly relied on passive identification of symptomatic cases, monitoring and contact tracing. To better control and manage the SARS-CoV-2 pandemic, the effectiveness and cost-effectiveness of active surveillance strategies of the wider population (i.e., to identify and isolate infected individuals regardless of symptoms) should be evaluated in order to guide the improvement of preventive strategies [34,35]. A systematic review and meta-analysis that evaluated the prevalence of symptoms among adults infected by SARS-CoV-2 found fever (78% [95% CI: 75%-81%]),…”
Section: Plos Onementioning
confidence: 99%
“…on the accuracy of PCR testing (Alcoba-Florez et al, 2021;Barak et al, 2021;Borillo et al, 2020;Deckert et al, 2021;Kagan et al, 2021;Lim et al, 2020). Previous studies have indicated that a pool size of 10 and below is necessary to maintain sensitivity and cost-effectiveness of pooled testing (Barak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%